2018
DOI: 10.4209/aaqr.2017.09.0322
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wintertime Polluted Aerosol on Clouds over the Yangtze River Delta: Case Study

Abstract: The effects of aerosol on clouds are examined over the Yangtze River Delta (YRD) using 3 months of satellite data from the polluted wintertime from December 2013 to February 2014. The relationships between aerosol properties, and cloud micro-and macro-physical parameters are analyzed in detail to clarify the differences in cloud development under various aerosol and meteorological conditions. Complex relationships between the aerosol optical depth (AOD), and the cloud droplet radius (CDR), liquid water path (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…During the period of March-April-May (MAM), higher CO concentrations are observed (Figure 2a) in countries south of China, such as Myanmar and Laos and over Europe. In [82], the authors also studied aerosols in China, focusing on the Yangtze River Delta in December 2013 and January 2014. They found that dust aerosols in that region make little difference to cloud properties, and the primary source is anthropogenic activities.…”
Section: Seasonal and Spatial Variations Of Global Co (Observations A...mentioning
confidence: 99%
“…During the period of March-April-May (MAM), higher CO concentrations are observed (Figure 2a) in countries south of China, such as Myanmar and Laos and over Europe. In [82], the authors also studied aerosols in China, focusing on the Yangtze River Delta in December 2013 and January 2014. They found that dust aerosols in that region make little difference to cloud properties, and the primary source is anthropogenic activities.…”
Section: Seasonal and Spatial Variations Of Global Co (Observations A...mentioning
confidence: 99%